Real-Time Frequency Adjustment of Images and Videos - Germano, Rafael L.; Gastal, Eduardo S. L. (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2021: Anais Estendidos da XXXIV Conference on Graphics, Patterns and Images, 2021)
We present a technique for real-time adjustment of spatial frequencies in images and videos. Our method allows for both decreasing and increasing of frequencies, and is orthogonal to image resizing. Thus, it can be used to automatically adjust spatial frequencies to preserve the appearance of structured patterns during image downscaling and upscaling. By pre-computing the image's space-frequency decomposition and its unwrapped phases, these operations can be performed in real time, thanks to our novel mathematical perspective on frequency manipulation of digital images: interpreting the problem through the theory of instantaneous frequencies and phase unwrapping. To make this possible, we introduce an algorithm for the simultaneous phase unwrapping of several unordered frequency components, which also deals with the frequency-sign ambiguity of real signals. As such, our method provides theoretical and practical improvements to the concept of spectral remapping, enabling realtime performance and improved color handling. We demonstrate its effectiveness on video and a large number of images subject to frequency adjustment. By providing real-time control over the spatial frequencies associated with structured patterns, our technique expands the range of creative and technical possibilities for image and video processing.